Identity Infrastructure Boost Concept for eduroam Service - Petrosyan, Arthur S.; Petrosyan, Gurgen S.; Tadevosyan, Robert N.; Arsalanian, Kevork Kh. (Mathematical Problems of Computer Science, 2021)
This paper presents the concept of authenticating eduroam users via their organization’s IMAP server. The concept described is based on the fact that most organizations, even lacking their own personnel identity database, have at least an email service in place and, thus, have a working IMAP server for their organization domain name. Thus, the existing email username/password within a particular organization can be used as an identity source for eduroam authentication. The paper describes the components required to implement the concept, as well as some expected limitations for this solution. The concept is planned to be implemented in ASNET-AM network in order to stimulate more rapid use of eduroam service in Armenia